PEMERANAN TOKOH ROBERT DALAM NASKAH A LIFE IN THE THEATRE KARYA DAVID MAMET - Abani, Kevin; Nurcahyono, Wahid; Rossadi, Rukman (Institut Seni Indonesia Yogyakarta, 2022)
A Life In The Theater by David Mamet is a theater script that tells about the problems of a stage actor's life between teacher and student that describes friendship, growth, development, and the human condition in life as a stage actor. To realize the character of Robert in the script of A Life In The Theater by David Mamet, the author uses the acting theory of Stanislavski The System, which is a systematic approach to training actors. In the process of playing the role, the magic if method is used, namely the ability to imagine the character is in a series of fictional situations and imagine how and what the character will do in dealing with the situation. Keywords: Actor, A Life In The Theatre, David Mamet, The System, Magic If